2011
DOI: 10.1159/000331047
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of CINtec® PLUS p16INK4a/Ki-67 Double-Staining in Cytological Screening of Cervical Cancer

Abstract: Objective: This study evaluated the usefulness of p16INK4a/Ki-67 as a new biomarker in the diagnosis of human papillomavirus (HPV)-related cervical lesions. Study Design: From 69 women with previous positive cytology, clinician-collected (CC) samples were obtained using a Cervex-Brush®. One month later, self-collected (SC) material was acquired using a Rovers® Viba-Brush. Liquid-based cytology specimens were prepared from both samples, and then the grades of squamous intraepithelial lesions (SIL) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 90 publications
2
15
1
1
Order By: Relevance
“…Various studies have evaluated the usefulness of the immunocytochemical detection of the biomarkers p16 and Ki-67 as potential indicators of an underlying high-grade cervical lesion. [29][30][31][32] In our study, dual staining was expressed in 36.1% of LSIL cases, which is consistent with the result of 36.4% reported by Singh et al 35 However, higher p16/Ki-67 positivity rates of 52.5%, 66.5% and almost 70% were detected in other studies. [30][31][32][33] In those studies, immediate or subsequent clinical outcome was more frequently CIN2+ compared with our results.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Various studies have evaluated the usefulness of the immunocytochemical detection of the biomarkers p16 and Ki-67 as potential indicators of an underlying high-grade cervical lesion. [29][30][31][32] In our study, dual staining was expressed in 36.1% of LSIL cases, which is consistent with the result of 36.4% reported by Singh et al 35 However, higher p16/Ki-67 positivity rates of 52.5%, 66.5% and almost 70% were detected in other studies. [30][31][32][33] In those studies, immediate or subsequent clinical outcome was more frequently CIN2+ compared with our results.…”
Section: Discussionsupporting
confidence: 91%
“…In recent studies, it has been shown that the sensitivity of p16/Ki-67 dual staining for the detection of CIN2+ is close to that of hrHPV positivity, and ranges from 81.8% to 97%; the specificity ranges from 53% to 81.8% and, in all studies, is higher for p16/Ki-67 dual staining than for hrHPV DNA tests (specificity of about 40%). [30][31][32][33][34][35] Similarly, in our study, the sensitivity of p16/Ki-67 dual staining was comparable to that of the hrHPV test, and the specificity was substantially higher. The highest specificity was found for presence of the HPV16 genotype (91%), but with low sensitivity.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The threshold for positivity of the assay is the presence of p16 and Ki-67 in one single cell [57-60,65,67,69], which emphasizes the need for sufficient cellularity of specimens with sufficient intact abnormal cells to guarantee the clinical applicability of this triage strategy. Concordantly, p16/Ki-67 dual-stained cytology is not reliably applicable to self-sampled material [70]. Although data on the long-term ≥CIN3 risk in p16/Ki-67 dual-stain negative women are currently lacking, results from the studies with short-term follow-up (up to 2 years) [65] are promising, reporting NPVs of a single p16/Ki-67 dual-stained cytology test between 97.4% and 99.4% [65,67].…”
Section: P16/ki-67 Dual-stained Cytologymentioning
confidence: 97%